Produção de biodiesel a partir de óleo residual de fritura utilizando o líquido iônico hidróxido de colina como catalisador - Bessa, Aline Mara Maia (2015)
The production of biodiesel is generally performed by alkaline transesterification oils with low amounts of free fatty acids (FFAs). In order to decrease the costs of production of biodiesel, low quality waste cooking oils or grease have been investigated as a source alternative, but problems in the purification step due to the formation of soap are found in catalysis with sodium hydroxide. In this work, the ionic liquid choline hydroxide was produced and used as catalyst in the production of biodiesel from oils of frying food. An experimental design was carried out to investigate the influence of variables: molar ratio oil/alcohol, temperature and concentration of catalyst in the conversion of triglycerides and free fatty acids to methyl esters. The concentration of catalyst showed higher influence on conversion, followed by the molar ratio of oil / alcohol. The temperature range did not result in significant conversion changes. The kinetic analysis showed that the highest conversions were obtained with 3 hours of reaction. The statistical design allowed find optimal conditions: 5.5% w/w catalyst molar ratio of oil/methanol 1:12, temperature 40 °C and 3 hours of reaction. Thermodynamic properties and acid numbers were determined for reaction products of the reactions carried out in experimental design, in order to provide data for process control. The acid numbers of products of all reactions were significantly reduced, independent of conversion. To evaluate the possibility of recovery and reuse of the ionic liquid, the liquid-liquid equilibrium of systems containing water, 1-butanol and glycerin, water, 1-butanol and choline hydroxide, and the partition in the ionic liquid system water, 1-butanol and glycerin at 30 ° C were studied. The solubility of the components was evaluated by construction of the binodal curve and the compositions of the equilibrium phases were determined by densitometry. The results show that glycerin is distributed preferably in the phase rich in water and it was not possible to quantify all compositions the water phase system, 1-butanol and choline hydroxide in the case that an electrolytic system